Evaluating the safety effectiveness of downgrade warning signs on vehicle crashes on Wyoming mountain passes. Issue 1 (1st January 2019) - Moomen, Milhan; Rezapour, Mahdi; Raja, Mustaffa Ngah; Ksaibati, Khaled
Abstract: Highway safety on mountain passes is a major concern to most highway agencies in the Western United States. Large trucks are known to be disproportionately affected on downgrades which characterize mountain passes in comparison to other vehicle classes. However, downgrade crash risks are known to exist also for several other classes of vehicles such as buses, single-unit trucks, recreational vehicles (RVs) and passenger vehicles. The Wyoming Department of Transportation (WYDOT) in an effort to reduce the crash risks existing on Wyoming mountain passes has among other measures installed warning signs on steep grades in the state. However, concerns for out of control vehicles on downgrades persists. An empirical analysis of the safety performance of static warning signs installed two-lane road downgrades was carried out using the negative binomial (NB) modeling approach. A review of the literature indicated that there are unique contributory factors to truck and non-truck crashes. Two crash prediction models were therefore developed each for truck and other vehicles. In an attempt to approach the study holistically and to derive reliable results, traffic and geometric factors were included in the analysis. The results showed that truck escape ramp, directional and speed combination, and hill combination warning signs are effective in reducing truck crashes on downgrades. For non-truck crashes, the presence of downgrade and truck-specific warning signs within 0.5 miles of the downgrade, hill, chevron, and directional and speed combination warning signs reduce crashes to various degrees. It is hoped that this study will provide important information to traffic safety engineers and policymakers concerned with downgrade safety.